2021
DOI: 10.1111/pai.13492
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and exercise‐induced bronchoconstriction – Is there a link?

Abstract: Background The objective of this study was to evaluate the role of body mass index with regard to exercise performance, exercise‐induced bronchoconstriction (EIB), and respiratory symptoms in 7‐ to 16‐year‐old children. Methods A total of 1120 outdoor running exercise challenge test results of 7‐ to 16‐year‐old children were retrospectively reviewed. Lung function was evaluated with spirometry, and exercise performance was assessed by calculating distance per 6 minutes from the running time and distance. Respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Unsurprisingly, the VO2max was lower in children with high BMI, as adipose tissue does not consume oxygen, as well as in girls, reflecting the well-known gender differences in muscle mass and adipose tissue.9 31 Exercise-induced symptoms may be associated with misdiagnosis of asthma in overweight subjects. 32 Therefore, in this study, CPET parameters' comparisons used generalised linear models adjusted not only on gender and age, but also on BMI, in order to determine the impact of paediatric asthma on aerobic fitness. Interestingly, the results of this study suggest the existence of an early onset of physical deconditioning in childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, the VO2max was lower in children with high BMI, as adipose tissue does not consume oxygen, as well as in girls, reflecting the well-known gender differences in muscle mass and adipose tissue.9 31 Exercise-induced symptoms may be associated with misdiagnosis of asthma in overweight subjects. 32 Therefore, in this study, CPET parameters' comparisons used generalised linear models adjusted not only on gender and age, but also on BMI, in order to determine the impact of paediatric asthma on aerobic fitness. Interestingly, the results of this study suggest the existence of an early onset of physical deconditioning in childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent large birth cohort study by Eijkemans et al [28] reported that whilst physical activity at early school age was not associated with asthma development later in life, sedentary activity time was associated with worse lung function (i.e., lower FEV 1 /FVC ratio). Several recent studies also report an association between BMI, physical activity engagement and asthma control [13,14,[29][30][31][32][33][34]. Indeed, Zhang et al [35] highlighted that physical activity is associated with improved asthma control in children, particularly in those with a high BMI.…”
Section: Physical Activity Profiles In People With Asthmamentioning
confidence: 98%
“…Since 2020, six observational studies have evaluated functional and/ or exercise capacity in people with asthma [12][13][14][15][16][17] (Table 1). Gianfrancesco et al [12] assessed functional capacity via the 6-min walk test and Glittre ADL-test (TGlittre) in a large cohort of children and adolescents (aged 7-17 years).…”
Section: Functional and Exercise Capacity In People With Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…In an overweight individual, intense physical exercise as running might trigger coughing and breathlessness, which, in children, is difficult to distinguish from asthma symptoms without taking objective lung function measurements [ 21 ]. In children with asthma, physical activity may also trigger these symptoms, leading to wheezing and breathlessness, which could result in the individual refraining from more intense exercise or physical activity.…”
Section: Introductionmentioning
confidence: 99%